Adipose tissue fibrosis, hypertrophy, and hyperplasia: Correlations with diabetes in human obesity. Issue 3 (March 2016) - Muir, Lindsey A.; Neeley, Christopher K.; Meyer, Kevin A.; Baker, Nicki A.; Brosius, Alice M.; Washabaugh, Alexandra R.; Varban, Oliver A.; Finks, Jonathan F.; Zamarron, Brian F.; Flesher, Carmen G.; Chang, Joshua S.; DelProposto, Jennifer B.; et al.
Abstract : Objective: The relationship between adipose tissue fibrosis, adipocyte hypertrophy, and preadipocyte hyperplasia in the context of obesity and the correlation of these tissue‐based phenomena with systemic metabolic disease are poorly defined. The goal of this study was to clarify the relationship between adipose tissue fibrosis, adipocyte hypertrophy, and preadipocyte hyperplasia in human obesity and determine the correlation of these adipose‐tissue based phenomena with diabetes. Methods: Visceral and subcutaneous adipose tissues from humans with obesity collected during bariatric surgery were studied with QRTPCR, immunohistochemistry, and flow cytometry for expression of collagens and fibrosis‐related proteins, adipocyte size, and preadipocyte frequency. Results were correlated with clinical characteristics including diabetes status. Results: Fibrosis was decreased, hypertrophy was increased, and preadipocyte frequency and fibrotic gene expression were decreased in adipose tissues from diabetic subjects compared to non‐diabetic subjects. These differences were greater in visceral compared to subcutaneous adipose tissue. Conclusions: These data are consistent with the hypothesis that adipose tissue fibrosis in the context of human obesity limits adipocyte hypertrophy and is associated with a reciprocal increase in adipocyte hyperplasia, with beneficial effects on systemic metabolism. These findings suggest adipose tissue fibrosis as a potential target for manipulation of adipocyte metabolism.